Kontribusi Nilai Uji Tulis Penerimaan Mahasiswa Baru Dengan Hasil Indeks Prestasi Kumulatif Dan Objective Structured Clinical Examination Terhadap Kelulusan Mahasiswa - Deni Alamsyah (Jurnal Terapi Wicara, 2025)
Background: Student success in achieving academic achievement is influenced by two factors, namely internal factors arising from within the student, such as health, motivation, interest, and learning ability, and external factors arising from the surrounding environment, such as family, social, economic, and campus conditions. Objective: This study aims to analyze the relationship between the written test scores of New Student Admissions (PMB) and the Grade Point Average (GPA) and Objective Structured Clinical Examination (OSCE) scores of vocational graduates of the D3 speech therapy study program. Method: This study used a quantitative approach with a correlational and predictive regression design, involving 39 students. Data were obtained from graduates of the D3 Speech Therapy program and analyzed using SPSS 26 software. Pearson's correlation coefficient was used to measure the relationship between PMB written test scores and scores on various final exam components (GPA) and (OSCE). Results: There is a significant positive correlation between PMB and GPA with an r value (37) where rcount > rtable = 0.40 > 0.316, while the p value <  = 0.012 < 0.05. There is no significant relationship between PMB and OSCE, with a value of r (37) where rcount < rtable = 0.10 < 0.316, while the value of p >  = 0.56 > 0.05. However, GPA has a strong positive relationship with OSCE, with a value of r (37) where rcount > rtable = 0.58 > 0.316, while the p-value < α = 0.001 < 0.05. Descriptive statistics show that there is a significant positive correlation between PMB and GPA, but not between PMB and OSCE. Furthermore, GPA has a strong relationship with OSCE, indicating that academic achievement is related to clinical competence. Conclusion: Respondents demonstrated high academic and clinical achievement. There is a moderate positive correlation between PMB and GPA, but no significant relationship between PMB and OSCE. However, GPA is strongly correlated with OSCE, indicating that good academic performance is associated with higher clinical competence.